Cuidados de enfermería y satisfacción del paciente post operado mediato - Díaz Quiliche, Miriam Elizabeth (2020)
This research study is descriptive correlational cross-sectional, was performed with post- operated patients mediates service Surgery A and B Víctor Lazarte Echegaray Hospital during the months of September - November 2017. The sample consisted of 155 patients post mediated operations, which made up the sample universe. The instrument used was the survey: Forbes Patient Satisfaction and Care Q Quality of Care, the results were reported in graphs with percentage frequencies. In the statistical analysis, the Chi – square criteria that measures the relationship between two variables were applied. From the analysis of the result it is concluded: That the degree of nursing care in its presented dimensions, shows that 66% are suitable and 34% are inadequate, likewise the level of satisfaction of the post-operated patient who is bad with 7.7%, regular 54.8% and good 37.4%, so it was shown that there is a relationship between the degree of nursing care and its dimensions with the level of satisfaction.